Harmonizing Drug Safety and Data Integrity: A Review on the Integration of Pharmacovigillance and Clinical Data Management - Samanta, Souman; Sah, Sneha (Indian Journal of Pharmacy Practice)
Pharmacovigilance (PV) and Clinical Data Management (CDM) are increasingly linked domains that are of enormous importance in ensuring the safety of drugs throughout the entire process. In the review, the evolving landscape of pharmacovigilance is reviewed with significant aspects such as Adverse Drug Reactions (ADRs), signal discovery, post-marketing surveillance, and the regulatory framework stipulated by the WHO, EMA, and USFDA. It demonstrates the value of standard codes such as MedDRA and the E2B (R3) format in normalizing the way that safety reports are submitted on a global scale. Data capture, data cleaning, or database locking CDM practices can be used to generate quality clinical datasets required in regulatory submissions. New technologies such as AI, machine learning, and blockchain are transforming not only PV and CDM by making the discovery of signals simpler, automating the process of reconciliation, and more easily tracing the data. The review shows it is paramount to share data and codes and establish interdepartmental cooperation to interface PV and CDM functions. Through identifying and resolving issues such as duplicated reporting, data inconsistency, and unified platforms, as well as real-time dashboards, the synergy between PV and CDM can be enhanced so as to make the patients safer, compliant with the regulations, and more efficient in operation.
Keywords: Pharmacovigilance; Clinical Data Management; Adverse Drug Reactions; Signal; Detection; Regulatory Compliance